Paired Teaching: A Professional Development Model for Adopting Evidence-Based Practices. Issue 3 (3rd July 2018) - Holland, Tara; Sherman, Sarah Bean; Harris, Sara
ABSTRACT: How can we best support instructors to learn, practice, and retain student-centered, active-learning teaching strategies in their undergraduate courses? While approaches like professional development workshops may inspire some, permanent adoption of new pedagogy is rare. Here, we investigate "paired teaching" to achieve adoption and continued use of evidence-based practices. In this model, an instructor with little or no experience in student-centered teaching is paired with an experienced instructor in a semester-long course that has established student-centered pedagogy. This study evaluates information from eight pairs of instructors over a three-year period. Data was collected before, during, and after the paired teaching semester through interviews, written reflections, and teaching observations. Results indicate that paired teaching is beneficial as a professional development model for new instructors who have little teaching experience. The teaching practice of these instructors evolved to be increasingly student-centered, and they continued to use this pedagogy in subsequent classes. More established instructors who were less familiar with active learning showed lower tendencies to incorporate new pedagogies into their existing classes. We suggest best practices to maximize benefits and mitigate challenges associated with paired teaching.